Reconstructing Christian Educational Philosophy in Contemporary Education: A Metaphysical, Epistemological, and Axiological Analysis of Learning, Worldview, and Teacher Identity - Lilik Kusnadi (Published by Institut Teknologi Pendidikan Indonesia, 2026)
Contemporary education has been profoundly influenced by modern educational philosophies, including progressivism, constructivism, and humanism, which have generated numerous pedagogical innovations such as active learning, problem-based learning, cooperative learning, and critical thinking. Although these instructional approaches have enhanced student engagement and cognitive development, their philosophical assumptions frequently differ from the biblical worldview that underpins Christian education. This study aims to examine Christian educational philosophy from the perspectives of metaphysics, epistemology, and axiology, compare it with major contemporary educational philosophies, and develop a conceptual framework that enables the adoption of pedagogical innovations while preserving the theological integrity of Christian education. The study employed a qualitative library research approach using philosophical-theological analysis. Data were collected from primary and secondary literature on Christian educational philosophy, contemporary educational philosophies, learning theories, and the integration of faith and learning. The findings indicate that Christian educational philosophy is grounded in a biblical worldview that affirms God as ultimate reality, divine revelation as the foundation of truth, and the restoration of the Imago Dei as the supreme purpose of education. Comparative analysis demonstrates that contemporary instructional strategies may be appropriately adopted when critically evaluated through biblical principles. As its principal conceptual contribution, this study proposes the Biblical Worldview Filtering Framework (BWFF), which distinguishes pedagogical methodology from philosophical commitment and provides a systematic framework for integrating educational innovations without compromising Christian identity. Furthermore, the study argues that Christian teacher identity constitutes an essential component of institutional worldview consistency, educational mission, and curriculum implementation rather than merely an employment qualification. The study concludes that Christian education is fundamentally worldview-centered rather than methodology-centered, integrating biblical truth, pedagogical innovation, professional competence, spiritual formation, and institutional coherence to achieve holistic educational excellence.